Draft Fourth Plan Material and Financial Balances 1964-65, 1970-71 and 1975-76 - Planning Commission (Planning Commission, 1966)
The Draft Outline of the Fourth Five Year Plan presented to the Parliament describes the general considerations shaping the approach to the Fourth Plan, the main features of the proposed programme and the major policy issues involved in the pursuit of specified objectives. Being intended for the public at large, the Draft Outline dealt with these matters in non-technical terms. The rationale of the programme was explained in rather broad terms. The basis for arriving at particular targets was not spelled out. Nor was an attempt made to show in detail the internal consistency and balance of the Plan in its different aspects.
Perspective Planning Division, Planning Commission, Government of India